2016
DOI: 10.1111/nyas.13278
|View full text |Cite
|
Sign up to set email alerts
|

Cartilage extracellular matrix as a biomaterial for cartilage regeneration

Abstract: The extracellular matrix (ECM) of various tissues possesses the model characteristics that biomaterials for tissue engineering strive to mimic; however, owing to the intricate hierarchical nature of the ECM, it has yet to be fully characterized and synthetically fabricated. Cartilage repair remains a challenge because the intrinsic properties that enable its durability and long-lasting function also impede regeneration. In the last decade, cartilage ECM has emerged as a promising biomaterial for regenerating c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
49
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(52 citation statements)
references
References 57 publications
(173 reference statements)
2
49
0
1
Order By: Relevance
“…The differentiation and proliferation of ADSCs strengthened the compressive elastic moduli of scaffolds ( Figure 8B). Our results agree with previous studies showing that accumulated GAG and collagen content can improve the biomechanical property of scaffolds 3,41 and ADSCs seeded onto scaffolds can easily be differentiated into chondrocytes and induced to form new cartilage tissue with the addition of TGF-β3 ( Figure 5). of cartilage, the presence of these constituents can affect the secretion of GAG and collagen.…”
Section: Discussionsupporting
confidence: 83%
“…The differentiation and proliferation of ADSCs strengthened the compressive elastic moduli of scaffolds ( Figure 8B). Our results agree with previous studies showing that accumulated GAG and collagen content can improve the biomechanical property of scaffolds 3,41 and ADSCs seeded onto scaffolds can easily be differentiated into chondrocytes and induced to form new cartilage tissue with the addition of TGF-β3 ( Figure 5). of cartilage, the presence of these constituents can affect the secretion of GAG and collagen.…”
Section: Discussionsupporting
confidence: 83%
“…Due to these appropriate characteristics, there is a significant interest for using tissue decellularization to provide ECM-based scaffolds (Choi et al 2012; Costa et al 2007; Hellström et al 2014; Kiyotake et al 2016; Law et al 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Cartilage extracellular matrix (ECM), a specific mixture of substances secreted by the resident cells in cartilage, has emerged as an attractive biomaterial for cartilage regeneration. ECM contains the relevant bioactive factors and contributes to cell adhesion, proliferation and differentiation [28,29]. Several studies have revealed that cartilage ECM can enhance chondrogenic differentiation of stem cells [10,30,31].…”
Section: Introductionmentioning
confidence: 99%